DETERMINANTS OF STUDENT SAVING BEHAVIOR : THE INFLUENCE OF FINANCIAL LITERACY, FAMILY FINANCIAL SOCIALIZATION, SELF-CONTROL AND PEER INFLUENCE - Muhammad Luthfi Abdul Maajid; Lela Hindasah (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2026)
This study examines the influence of financial literacy, family financial socialization, self-control, and peer influence on saving behavior among university students at the Faculty of Economics and Business, Universitas Muhammadiyah Yogyakarta. Using survey data from 200 students collected during the 2022–2024 period, saving behavior is operationalized through saving frequency, motivation, objectives, and consistency. The data are analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings indicate that financial literacy exhibits a positive but statistically insignificant relationship with saving behavior, whereas family financial socialization, self-control, and peer influence demonstrate significant positive effects. The structural model accounts for 37.9% of the variance in saving behavior. Overall, the results suggest that behavioral and social factors play a more prominent role than financial knowledge alone in shaping students’ saving behavior, underscoring the importance of incorporating psychological and social dimensions into financial education initiatives